Surface modification of Al by high-intensity low-energy Ti-ion implantation: Microstructure, mechanical and tribological properties - Ryabchikov A. I. Aleksandr Ilyich; Kashkarov E. B. Egor Borisovich; Shevelev A. E. Aleksey Eduardovich; Obrosov A. Aleksey; Sivin D. O. Denis Olegovich (2019, 2019)
Title screen